Trans-differentiation Induction of Human-mesenchymal Stem Cells Derived from Different Tissue Origin and Evaluation of their Potential for Differentiation into Corneal Epithelial-like Cells - Sun-Woung Moon; Hyeon-Jeong Lee; Won-Jae Lee; Sun-A Ock; Sung-Lim Lee (The Korean Society of Animal Reproduction and Biotechnology, 2018)
The trans-differentiation potential of mesenchymal stem cells (MSCs) is employed, but there is little understanding of the cell source-dependent trans-differentiation potential of MSCs into corneal epithelial cells. In the present study, we induced trans-differentiation of MSCs derived from umbilical cord matrix (UCM-MSCs) and from dental tissue (D-MSCs), and we comparatively evaluated the in vitro trans-differentiation properties of both MSCs into corneal epithelial-like cells. Specific cell surface markers of MSC (CD44, CD73, CD90, and CD105) were detected in both UCM-MSCs and D-MSCs, but MHCII and CD119 were significantly lower (P < 0.05) in UCM-MSCs than in D-MSCs. In UCM-MSCs, not only expression levels of Oct3/4 and Nanog but also proliferation ability were significantly higher (P < 0.05) than in D-MSCs. In vitro differentiation abilities into adipocytes and osteocytes were confirmed for both MSCs. UCM-MSCs and D-MSCs were successfully trans-differentiated into corneal epithelial cells, and expression of lineage-specific markers (Cytokeratin-3, -8, and -12) were confirmed in both MSCs using immunofluorescence staining and qRT-PCR analysis. In particular, the differentiation capacity of UCM-MSCs into corneal epithelial cells was significantly higher (P < 0.05) than that of D-MSCs. In conclusion, UCM-MSCs have higher differentiation potential into corneal epithelial-like cells and have lower expression of CD119 and MHC class II than D-MSCs, which makes them a better source for the treatment of corneal opacity.